Between Ushlub Tahlili and Maudhu‘i: Which One Is More Relevant to Nowadays? Antara Ushlub Tahlili dan Maudhu‘i: Manakah yang Lebih Relevan dengan ‘Zaman Now’? - Sansan Ziaul Haq; Irham Irham; Yudril Basith (Institut Agama Islam Negeri Kerinci, 2022)
The demand for renewal of the methodology of Qur’anic interpretation is a modern phenomenon. The Qur’an as the main source of Islamic teachings is fixed and does not change, but on the other hand, the dynamics of the times require the Qur’an to answer new problems. This is what then encourages the experts to review how to present the guidance of the Qur’an in the current context. Among these various updates are those related to the techniques of presenting interpretations (asalib al-tafsir). This paper specifically examines and compares the two most popular techniques of Quranic interpretations, namely ushlub tahlili and ushlub maudhu'i. Regarding these two techniques, some experts consider that the second is more relevant to the demands of nowadays than the first. However, this paper analytically concludes that these two techniques cannot be compared to negate each other because each has advantages and disadvantages. In fact, this two ushlub are still in use, with various adjustments, so that they are considered relevant in the midst of the times.